La fonction de l’Inspecteur général des Institutions financières - Bouchard, Jean-Marie (Assurances, 1983)
Mr. Jean-Marie Bouchard describes the new duties of the lnspector General of Financial Institutions of Quebec. In particular, he points out that the monitoring of insurance will be the duty of an insurance superintendent while deposit institutions will come under another civil servant of the same rank.